Structural and Antibacterial Studies of Cu(II) Macrocyclic Complexes - Ambwani, Jitendra; Bansal, N.L.; Kaushik, Kshama (Asian Journal of Chemistry, 2010)
Two new macrocyclic complexes of Cu(II) with the composition Cu[DPAIDAH](BF4)2 and Cu[DPADTPH](BF4)2 (where [DPAIDAH] = diphenyl diacetic acid-2,2'-imino diacetic acid dihydrazone and [DPADTPH] = diphenyl diacetic acid-2,2'-dithio dipropionic acid dihydrazone have been synthesized. The complexes' have been characterized on the basis of elemental studies, IR spectral analysis and electronic spectra. The in vitro antimicrobial studies revealed that the macrocyclic complexes are potentially active against a few bacteria and fungi and exhibit greater biocidal effect as compared to the ligand fragments.